Forestry as an Instrument of Social Change - Shah, S. A. (Indian Forester, 1975)
Social justice implies the obligation to provide for the minimum needs which include cooking fuel, small timber for rural housing and agricultural implements, grass, grazing etc. which contribute to the stability of the life of the rural poor. Forestry has a role to play in meeting some of these basic needs. Various activities associated directly or indirectly with forestry have the potential of increasing the earnings of the tribals and other backward sections of the population. The labour intensiveness of the forestry operations is reflected by the fact that one hectare of potentially exploitable forest can generate an employment of 850 man-days in the primary sector itself, let alone the processing of the raw materials resulting therefrom, Cottage and small scale industries based on forest raw materials are capable of bringing employment to the very door step of the rural poor. Such industries do not entail heavy investments, sophisticated machinery or skills of any high degree. Bidi manufacture, tasar rearing, rope making, toy making, bamboo furniture making, etc., are but a few examples of such industries. Forestry, therefore, can be commissioned to reduce the disparity between the haves and the have-note and thus can serve as a powerful instrument of social change.